Hubungan Senam Yoga Dengan Kualitas Tidur Malam Hari Pada Anggota Yang Mengalami Insomnia Di Sanggar Senam RM7 Karanganyar - Rahmarwati, Fresha Putri; , Dwi Rosella K, S.St FT., M.Fis; , Dwi Kurniawati, SSt.FT (2016)
Background: Many factors cause our body disorder or trouble sleeping the night is often called insomnia . As a result of insomnia sufferers sleep quality to be bad . Quality is the ability of each individual to maintain a state of sleep and to get REM and NREM sleep stage right . Many factors that cause insomnia include stress , illness , age , lifestyle and others.Objective: To determine the correlation of yoga exercises with the quality of nighttime sleep at members who have insomnia . Aims Research: For information and evaluation that yoga exercise can improve sleep for people with insomnia . Research Method: This was an observational study by distributing questionnaires and questionnaires with respondents . Sampling technique using purposive sampling as many as 60 respondents . Measuring tool by using a questionnaire or a questionnaire PSQI( Pittsburgh Sleep Quality Index) . The used statistical test is the test of Rank Correlation Test ( Spearman ) . Results: Based on the test staistik yoga exercises relationship with sleep quality produce p -value -0.048 or problabilitas < 0.05 . Conclusions: There is a relationship between yoga exercises with the quality of nighttime sleep at members who experience insomnia at RM7 Karanganyar gymnasium . Keywords: Gymnastics Yoga , Insomnia , Sleep Quality .